The Effect of Task Complexity on the Accuracy of the FL Oral Output of Advanced Iraqi Learners - Jassim Mohammed, Lect. Bahija; A. Abdul-Sattar, Prof. Dr. Mohammed (Basra studies journal, 2022)
This study explores the effect of task complexity on the FL oral output of a group of advanced Iraqi EFL learners in a task-based language teaching\learning framework. Its aim is to investigate the accuracy of the FL oral output of these learners with the increasing of task complexity (manipulated by topic familiarity) by employing two oral monologic tasks in the form of picture descriptions. One of the tasks is familiar and the other is unfamiliar in topic. A number of measures of accuracy (the number of clauses, the number of errors, the percentage of errors, the number of AS-units, the number of words, the number of error-free clauses, and the percentage of words to the As-units) are used for this purpose. The data is collected electronically due to quarantine following the spread of corona pandemic. The study follows a quantitative research method. Paired-samples t-tests are conducted to detect any significant differences in the participants' output between the two tasks. The findings show that increasing task complexity has positively affected all measures of accuracy. These findings are useful in exploring the extent to which FL performance can be affected by increasing task complexity.